Management of immune thrombocytopenia in adults: a population‐based analysis of the French hospital discharge database from 2009 to 2012. (31st March 2015) - Michel, Marc; Suzan, Florence; Adoue, Daniel; Bordessoule, Dominique; Marolleau, Jean‐Pierre; Viallard, Jean‐François; Godeau, Bertrand
Summary The present study describes the current clinical practice and hospital management of adults with immune thrombocytopenia (ITP) between 2009 and 2012 in France, based on the national discharge hospital database. Adult ITP patients were managed almost exclusively in public hospitals. A relatively stable number of patients, around 3200 per year, were hospitalized for ITP annually over the 4‐year period, about two‐thirds of whom were newly‐diagnosed ITP. Re‐hospitalizations tended to decrease over the study period. Intravenous immunoglobulin administration, concerning half of ITP hospitalized patients, and rituximab administration were stable over time, whereas a slight decrease of splenectomies was observed.